Familial giant hypertrophic gastritis (Ménétrier's disease). Issue 11 (November 1987) - Larsen, B; Tarp, U; Kristensen, E
Abstract : Familial giant hypertrophic gastritis involving three generations is reported. A review of the literature, where approximately 200 cases are described, showed only few cases of familial occurrence of this disease, and only in siblings. Our findings suggest dominant heredity, but considering the sparsity of familial occurrence reported earlier, heredity seems to be of only minor pathogenetic significance.